2005
DOI: 10.1590/s0034-89102005000300005
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de medicamentos no período de internação para o parto

Abstract: Descritores Uso de medicamentos. Gravidez. Lactação. Puerpério. Hospitalização. Maternidades. Anestesia. Cesárea. Parto. ResumoObjetivo O consumo de medicamentos no parto tem sido pouco explorado na literatura. Limitado no tempo e nas possibilidades terapêuticas, representa um evento privilegiado para discussão sobre o seu uso correto. Assim, realizou-se análise do consumo de medicamentos no parto, estabelecendo base para comparações entre maternidades. Métodos Estudo transversal envolvendo duas maternidades, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
1
3
1
2
Order By: Relevance
“…The mean number of drugs used was higher in SUS hospitalizations, both in prepartum/during delivery and postpartum periods, inconsistently with the findings of Perini et al 8 , which showed higher mean number of drugs in private hospitals in both periods. It is important to consider that the mean number of drugs in our study was higher in medical school hospitals, whose hospitalizations are mainly by the SUS.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The mean number of drugs used was higher in SUS hospitalizations, both in prepartum/during delivery and postpartum periods, inconsistently with the findings of Perini et al 8 , which showed higher mean number of drugs in private hospitals in both periods. It is important to consider that the mean number of drugs in our study was higher in medical school hospitals, whose hospitalizations are mainly by the SUS.…”
Section: Discussioncontrasting
confidence: 74%
“…The characterization of drug prescription during delivery hospitalization has been little investigated, in comparison with drug use throughout gestation 8 , 9 . This difference may be explained, in part, by the higher importance attributed to the teratogenic risks of drugs 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palavras-chave: uso de medicamentos; Assistência Farmacêutica; pós-parto; saúde do lactente; segurança do paciente INTRODUÇÃO O uso de medicamentos, tanto durante a gravidez quanto durante parto e puerpério, é de grande importância nos contextos clínico e biopsicossocial e deve ser sempre avaliado devido aos riscos e benefícios envolvidos. No pós-parto, o uso de medicamentos pode ocorrer, devido à necessidade de tratamento para combater infecções, depressão, além de doenças crônicas que requerem medicamentos de uso contínuo (1)(2)(3)(4)(5)(6).…”
unclassified
“…Já em 1972, Dias e colaboradores identificaram que as práticas de uso de fórceps e de realização de cesáreas eram mais comuns em hospitais privados do que nos públicos. Outros estudos confirmam que hospitais privados tendem a ser mais intervencionistas (Chacham & Perpétuo, 1996;D'Orsi et al, 2005) e a usar mais medicamentos durante a assistência ao parto (Perini, Magalhães & Noronha, 2005).…”
unclassified